Proceedings of the 23rd ACM Symposium on Virtual Reality Software and Technology 2017
DOI: 10.1145/3139131.3139137
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of exceptional motion in VR video contents for VR sickness assessment using deep convolutional autoencoder

Abstract: This paper proposes a new objective metric of exceptional motion in VR video contents for VR sickness assessment. In VR environment, VR sickness can be caused by several factors which are mismatched motion, field of view, motion parallax, viewing angle, etc. Similar to motion sickness, VR sickness can induce a lot of physical symptoms such as general discomfort, headache, stomach awareness, nausea, vomiting, fatigue, and disorientation. To address the viewing safety issues in virtual environment, it is of grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The extracted features were regressed onto subjective sickness scores, which were obtained from the deployment of a post-questionnaire. Kim et al [ 27 , 28 ] defined a concept of exceptional motion in VR content, and they predicted it by deploying an auto-encoder. The latent variables of their model were learned from easily downloadable scenes, and the results showed that the inferred exceptional motion was correlated with cybersickness.…”
Section: Introductionmentioning
confidence: 99%
“…The extracted features were regressed onto subjective sickness scores, which were obtained from the deployment of a post-questionnaire. Kim et al [ 27 , 28 ] defined a concept of exceptional motion in VR content, and they predicted it by deploying an auto-encoder. The latent variables of their model were learned from easily downloadable scenes, and the results showed that the inferred exceptional motion was correlated with cybersickness.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the literature shows that ML techniques have extensively been used for the QoE prediction of VR videos [36]- [38]. The previous researches in [39]- [42] presents the capability of various ML algorithms to classify the values for QoE-affecting factors, such as video quality and stalling.…”
Section: B Ml-based Qoe Prediction Methodsmentioning
confidence: 99%
“…As machine learning technology advanced, researchers have proposed solutions to predict cybersickness. Previous work demonstrated the viability to predict cybersickness (Padmanaban et al 2018;Kim et al 2017;Jin et al 2018). To improve user satisfaction with VR applications, it is important to develop solid objective metrics that can analyze and then predict the level of VR sickness when a user is exposed to VEs.…”
Section: Prediction Of Cybersicknessmentioning
confidence: 99%